Application of an Endodontic Static Guide in Fiber Post Removal from a Compromised Tooth - Mehran Farajollahi; Omid Dianat; Samaneh Gholami; Shima Saber Tahan (Case Reports in Dentistry)
Removing a fiber post from a root canal that requires endodontic retreatment is often very challenging. Conventional freehand techniques for removing fiber posts are time-consuming, sometimes result in iatrogenic errors, and heavily rely on the practitioner’s experience. The endodontic static guide can be an alternative method. While the use of an endodontic 3D-printed static guide for fiber post removal has been reported as highly successful, it can also cause complications. Skipping any critical steps during the guide construction or its clinical application can lead to errors. This case report presents the saving of a compromised tooth with a fractured fiber post and a periapical lesion around the apex through the use of an endodontic static guide for fiber post removal. This study describes possible sources of error that may happen during construction and clinical use of the guide.